(untitled) - Seidensticker, Edward (Cambridge, 1983)
Low City, High City is a lively and informal account of Tokyo's history from the end of the Tokugawa regime (in 1868) to the destruction of the city in the 1923 Kanto earthquake. During that half century, Tokyo was transformed from a feudal pre-industrial city of samurai and commoners to an imperial capital of bureacrats, businessmen, factory workers, and flappers. Seidensticker, a distinguished translator of Japanese literature, has written a highly readable cultural and social history of Tokyo that captures the colorful introduction of "Western" urbanism and chronicles the slowly fading old city. An absolute must for anyone with even a casual interest in Tokyo's past.
Keywords: Popular culture; Tokyo, Japan